IMPLEMENTATION AND DEVELOPMENT PROSPECTS OF DIGITAL SERVICES IN THE ACTIVITIES OF COMMERCIAL BANKS - Masharipova Nozima Ikramjon qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the theoretical and practical aspects of the implementation and development of digital services in commercial banks. The importance of digital banking in increasing financial efficiency, its role in creating convenience for clients, and the possibilities of reducing operating costs through the automation of service processes are highlighted. The introduction of mobile banking, internet banking, electronic wallets, and innovative payment systems in Uzbekistan and their significance in the development of the national financial sector are also highlighted. The research results reveal the future prospects of digital services and their significance in the transformation of banking business models.